A New Calcium Releasing Nano-composite Biomaterial for Bone Tissue Engineering Scaffolds - Cattalini, J. P.; Garcia, J.; Boccaccini, Aldo R.; Lucangioli, S.; Mourino (Procedia Engineering, 2013)
A biomaterial with bioactive glass nanoparticles (nBG) and Ca2+ incorporated into alginate matrix was developed. Films characterization was carried out by SEM, IR, tensile strength measurements, bioactivity assay, degradation and swelling studies. Ca2+ release from films was analyzed. Freeze-dried-scaffolds were also fabricated. Films showed the development of a homogeneous matrix and the mechanical properties were improved when nBG were incorporated. The bioactive nature of nBG containing films was confirmed by studies in simulated body fluid. Degradation was negligible and a good swelling capacity was observed. Moreover Ca2+ was released in a controlled manner. In scaffolds fabricated by freeze-drying, pores were seen to be uniform and well distributed. According to the characterization results, these composite biomaterials are attractive candidates for the fabrication of bone tissue engineering scaffolds. © 2013 The Authors.
UnivIS-Import:2015-03-09:Pub.2013.tech.IW.LM.anewca
Keywords: Biomaterials; Calcium; Composites; Films; Scaffolds